Legal Responsibility for the Perpetrators of Online Gambling Crimes in Indonesia - Seviana Ratna Intan (UM Purwokerto Press, 2023)
With the development of this technology, humans can easily access what they want, one of which is online gambling sites. Online gambling is a deviation that is contrary to religious, moral, moral and legal norms, but it is increasingly widespread and difficult to eradicate. Gambling is a form of community disease and is included in the qualification of crime. The rise of gambling will damage the social system of society itself. With the aim, the author is expected to provide usefulness to the development of legal science, especially in criminal law. Based on this, the author formulates the problem of factors causing online gambling and legal liability for online gambling offenders. From this writing, the research method used is normative juridical and statutory approaches, the data source that the author uses in this research is secondary data sources. Secondary data is obtained by conducting library research to obtain a theoretical basis. Based on the results of the research, the factors causing online gambling are divided into two, namely internal factors including intention, nature, talent, and emotional power, and also external factors including economic factors, social factors and facilities and infrastructure. Legal liability for online gambling offenders in Indonesia has been clearly and explicitly regulated in Article 303 paragraph (3) of the Criminal Code and Article 27 paragraph (2) of the Law on Electronic Information and Transactions.